Noncommutative aspects of Villadsen algebras - Ivanescu, Cristian; Kučerovský, Dan (My University, 2023)
In this short article, we survey the importance of Villadsen algebras in the context of the classification theory, with an emphasis on its non-commutative aspects.
Keywords: Villadsen algebras; classification theory